2018
DOI: 10.31895/hcptbn.13.3-4.8
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic profile of fresh chokeberry and chokeberry products

Abstract: Chokeberry (Aronia melanocarpa) fruits and its products are one of the richest sources of pholyphenols which may play important role in human health as for example in regulation of blood pressure levels, reducing concentrations of triglycerides, low density and total cholesterol. The objective of this study was to identify and quantify the content of pholyphenols, specifficaly phenolic acids (gallic, caffeic, p-coumaric, ellagic, chlorogenic) and flavonols (quercetin and kaempferol) using high performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The main phenolic compounds detected in aronia extract were catechin (828.49 µg/100 g DW), ferulic acid (296.24 µg/100 g DW), epicatechin (252.69 µg/100 g DW), salicylic acid (142.47 µg/100 g DW), protocatechuic (101.08 µg/100 g DW), ferulic acid methyl ester (79.57 µg/100 g DW), polydatin (68.28 µg/100 g DW), but also gallic, para-and meta-benzoic acids, procyanidin B1 and B2, etc. Tolić et al, identified and quantified polyphenolic compounds, especially gallic, caffeic, p-coumaric, ellagic, chlorogenic and flavonols acids (quercetin and kemferol) in two varieties of fresh aronia fruits (Nero and Viking variety) [5]. Ciocoiu et al, used high-performance liquid chromatogra-phy coupled with diode array detection and electrospray ionization-mass spectrometry (HPLC/DAD/ESI-MS) and identified five phenolic compounds in the ethanolic extract of aronia fruits as follows: chlorogenic acid, kuromanin, rutin, hyperoside and quercetin [40].…”
Section: Phenolic Content In the Aronia Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…The main phenolic compounds detected in aronia extract were catechin (828.49 µg/100 g DW), ferulic acid (296.24 µg/100 g DW), epicatechin (252.69 µg/100 g DW), salicylic acid (142.47 µg/100 g DW), protocatechuic (101.08 µg/100 g DW), ferulic acid methyl ester (79.57 µg/100 g DW), polydatin (68.28 µg/100 g DW), but also gallic, para-and meta-benzoic acids, procyanidin B1 and B2, etc. Tolić et al, identified and quantified polyphenolic compounds, especially gallic, caffeic, p-coumaric, ellagic, chlorogenic and flavonols acids (quercetin and kemferol) in two varieties of fresh aronia fruits (Nero and Viking variety) [5]. Ciocoiu et al, used high-performance liquid chromatogra-phy coupled with diode array detection and electrospray ionization-mass spectrometry (HPLC/DAD/ESI-MS) and identified five phenolic compounds in the ethanolic extract of aronia fruits as follows: chlorogenic acid, kuromanin, rutin, hyperoside and quercetin [40].…”
Section: Phenolic Content In the Aronia Extractmentioning
confidence: 99%
“…Among the polyphenols present in aronia, quercetin is the strongest antioxidant among the monomer phenolic compounds, followed by cyanidol-glucoside and chlorogenic acid [5]. Anthocyanins, flavonols and hydroxycinnamic acids contribute about 59.4% of the total antioxidant activity of aronia without assuming the possible synergism/antagonism between individual antioxidants [6].…”
Section: Introductionmentioning
confidence: 99%